Causality Inflation-Relative Prices: Comparative Evidence from Latin America - Dabús, Carlos Darío (2000)
In this paper we study the causality in the relation between inflation and relative price variability for six Latin-American countries with inflationary history: Argentina, Brazil, Peru, Mexico, Uruguay and Venezuela. The study is carried out in the framework of four inflationary regimes: moderate, high, very high and hyperinflation. There is a positive relation in most cases, with a systematic increase of price variability at higher inflation. Inflation volatility and the dummies that represent the regime of inflation are the best explanatory variables of relative price variability, while the causality analysis shows two main results: instantaneous causality and a Granger causality relation from inflation to price variability. In all cases the effect of inflation on relative prices is more significant in extreme inflation, so that the non-neutrality of inflation seems to be increasing with the level of inflation.